Analisis Kualitas Pelayanan Kesehatan Program Ambulans Gratis Lazismu Bantul Kota - Syifa, Nurus; Saharuddin, Erni (CV The Journal Publishing, 2024)
This research aims to analyze the quality of health services in the free ambulance program organized by LazisMu Bantul City. The research method used is descriptive analysis with a quantitative approach. The research population is the community using the free ambulance services of LazisMu Bantul City, with a sample of 69 individuals selected using accidental sampling techniques. Data collection was carried out through observation, documentation, and questionnaire filling. The measuring instrument used was a Likert scale questionnaire. Data were analyzed using descriptive analysis methods. The research results show that the average percentage of the reliability variable reaches 88.91%, placing it in the very good category, while responsiveness reaches 80.00%, which is still in the good category. The assurance variable, with an average percentage of 85.79%, is also considered very good, indicating that ambulance services provide strong assurance of the quality and safety of health services. The empathy variable of ambulance personnel also appears to be very good with an average percentage of 83.96%, while the tangibles variable reaches 100.00%, indicating very good and adequate physical quality and equipment of the ambulance. These findings can be used as a basis for improving the quality of free ambulance services in the future.